Profiling of Burkholderia cepacia Secretome at Mid-Logarithmic and Early-Stationary Phases of Growth - Mariappan, Vanitha (Public Library of Science, 2011)
BACKGROUND: Burkholderia cepacia is a Gram-negative pathogen that causes serious respiratory infections in immunocompromised patients and individuals with cystic fibrosis. This bacterium is known to release extracellular proteins that may be involved in virulence. METHODOLOGY/PRINCIPAL FINDINGS: In the present study, B. cepacia grown to mid-logarithmic and early-stationary phases were investigated on their ability to invade and survive intracellularly in A549 lung epithelial cells in order to discern the fate of these bacteria in the pathogenesis of B. cepacia lung infections in in vitro condition. The early-stationary phase B. cepacia was demonstrated to be more invasive than mid-logarithmic phase. In addition, culture supernatants of B. cepacia obtained from these phases of growth were also demonstrated to cause different cytotoxic potency on the A549 human lung epithelial cells. Profiling of the supernatants using the gel-based proteomics approach identified 43 proteins that were commonly released in both the growth phases and 40 proteins newly-released at the early-stationary phase. The latter proteins may account for the higher cytotoxic activity of the early-stationary culture supernatant compared to that obtained at the mid-logarithmic phase. Among the newly-released proteins in the early-stationary phase supernatant were flagellar hook-associated domain protein (FliD), flagellar hook-associated protein (FlgK), TonB-dependent siderophore (Fiu), Elongation factor G (FusA), phosphoglycerate kinase (Pgk) and sulfatase (AslA) which are known for their virulence. CONCLUSION/SIGNIFICANCE: Differences in the ability of B. cepacia to invade and survive intracellularly inside the epithelial cells at different phases of growth may improve our understanding of the varied disease progressions associated with B. cepacia infections. In addition, the identified culture supernatant proteins may be used as targets for the development of new strategies to control B. cepacia infection using agents that can block their release.